TREATMENT OF CAPRINE DYSTOCIA WITH SPECIAL REFERENCE TO C.S. - M. AL- Hamedawi, T.; J. Khammas, D. (The Iraqi Journal of Veterinary Medicine, 1994)
Cesarean section (C.S) was performed on 81 out of 172 case of caprine dystocia in local and shami breed goats, aged between 2-4 years old. The animals were brought in by owners and referred to Departmant of Theriogenology, College of Veterinary Medicine, University of Baghdad and another two Veterinary clinic centers around Baghdad during the kidding the kidding seasons of 1990-1993. C.S was a safe method of kid delivery with a high success rate (95%), followed by manual correction and traction (89.4%). The lowest response was obtained by pharmacological treatmant 46.6%. were The most common indications of C.S in does ring womb 45.5%, oversized fetus 35.8%, vaginal prolapse near the end of gestation 16% and fatal monsters 2.4%. C.S was performed more on primiparous does (39.6). Does having male kids appeared to be more likely to require C.S 61.3% than those having female kids 38.7%. rate of kids delivered by C.S was 66.8%. The obtained showed that C.S was most reliable and safe procedure to deal with dystocia in goats.